How Does International Capital Flow? - Michael Kumhof; Phurichai Rungcharoenkitkul; Andrej Sokol (ZBW - Leibniz Information Centre for Economics, 2021)
Understanding gross capital flows is increasingly viewed as crucial for both macroeconomic and financial stability policies, but theory is lagging behind many key policy debates. We fill this gap by developing a two-country DSGE model that tracks domestic and cross-border gross positions between banks and households, with explicit settlement of all transactions through banks. We formalise the conceptual distinction between cross-border saving and financing, which often move in opposite directions in response to shocks. This matters for at least four policy debates. First, current accounts are poor indicators of financial vulnerability, because in a crisis, creditors stop financing debt rather than current accounts, and because following a crisis, current accounts are not the primary channel through which balance sheets adjust. Second, we reinterpret the global saving glut hypothesis by arguing that US households do not finance current account deficits with foreigners' physical saving, but with digital purchasing power, created by banks that are more likely to be domestic than foreign. Third, Triffin's current account dilemma is not in fact a dilemma, because the creation of additional US dollars requires dollar credit creation by US and non-US banks rather than US current account deficits. Finally, we demonstrate that the observed high correlation of gross capital inflows and outflows is overwhelmingly an automatic consequence of double entry bookkeeping, rather than the result of two separate sets of economic decisions.
Keywords: E44; E51; F41; F44; 330; Bank lending; money creation; money demand; uncovered interest parity; exchange ratedetermination; international capital flows; gross capital flows